2013
DOI: 10.1159/000357259
|View full text |Cite
|
Sign up to set email alerts
|

Is It Necessary to Send Gallbladder Specimens for Routine Histopathological Examination after Cholecystectomy? The Use of Macroscopic Examination

Abstract: Background/Aims: Gallbladder specimens are routinely sent for histopathological examination after cholecystectomy in order to rule out the presence of gallbladder carcinoma (GBC). However, there is no evidence for the benefit of this costly practice. Our aim was to determine whether a selective strategy based on macroscopic appearance of gallbladder specimens is a reliable strategy to exclude them from histopathological examination. Methods: A retrospective study was conducted from January 2007 until November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…All cases of incidental GBC in these studies had a macroscopically abnormal gallbladder; hence, these studies suggest that it is safe to adopt a selective approach to Some studies showed that it may be justified to exclude gallbladder specimens from the HPE by using macroscopic examination. van Vliet et al have shown that of the 1375 gallbladder specimens examined macroscopically, not one incidental GBC is found (11). Of the 185 (13.5%) specimens of all gallbladder specimens that showed macroscopic abnormalities for which they would require further HPE in case of a selective policy, GBC was found in 6 specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases of incidental GBC in these studies had a macroscopically abnormal gallbladder; hence, these studies suggest that it is safe to adopt a selective approach to Some studies showed that it may be justified to exclude gallbladder specimens from the HPE by using macroscopic examination. van Vliet et al have shown that of the 1375 gallbladder specimens examined macroscopically, not one incidental GBC is found (11). Of the 185 (13.5%) specimens of all gallbladder specimens that showed macroscopic abnormalities for which they would require further HPE in case of a selective policy, GBC was found in 6 specimens.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a concern about the presence of early GBC in a normal-looking gallbladder specimen. However, simple cholecystectomy is considered adequate in these patients, and no further therapy is required (8,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…When GBC was suspected before or during surgery and diagnosed by intraoperative frozen-section biopsy, the surgery was immediately converted to open surgery and such patients were assigned to group I. 5 Reoperation was recommended for nearly all patients diagnosed with pT1b and pT2 lesions. The usual extent of reoperation included wedge resection of the gallbladder bed, regional lymph node dissection, removal of attached omental tissues, and optional extrahepatic bile duct resection (group III).…”
Section: Operationsmentioning
confidence: 99%
“…The observation of lack of malignancies further raises the question of any added value of routine histopathological examination of the resected part of the stomach after LSG as AbdullGaffar et al [18] implied. In light of financial restrictions that warrants evidence-based decision-making based on the cost-effectiveness concept, routine histopathological examination of surgical specimens has been previously questioned [24,25].…”
Section: Discussionmentioning
confidence: 99%